BAMBOO RESOURCES, CULTURAL VALUES, AND EX-SITU CONSERVATION IN BALI, INDONESIA - Wawan Sujarwo (BRIN Publishing (Penerbit BRIN), 2018)
SUJARWO, W. 2018. Bamboo resources, cultural values, and ex-situ conservation in Bali, Indonesia. Reinwardtia 17 (1): 67–75. — This present study describes the diversity of bamboo resources, based on Bali Botanic Garden’s bamboo collections, and its unusual uses, including complementary information on floristic region, and ex-situ conservation of bamboo resources on the island of Bali, Indonesia. Bamboo resources have played an important role in the economics and culture of rural communities in Bali. Bali Botanic Garden, Indonesian Institute of Sciences (LIPI), started to introduce bamboo species in 1982 and established the ex-situ conservation compartment (2 ha) of bamboo in the same year. Up to now, 52 species in 11 genera collected from mostly the Malesian region (67.44%) and the Eastern Asiatic region (20.93%) have been planted in the bamboo compartment, of which 5.77% bamboo species are woody climbers.